Fosfato natural reativo e fertilizantes nitrogenados no cultivo do capim-marandu - Cabral, Carlos Eduardo Avelino (2014)
Rock phosphate is fertilizer which can improve production forage grasses, by minimizing phosphorus fixation and reduce production cost. In highly weathered soils, such as Oxisols, the problem is severe, because occurs high phosphorus fixation in oxides, in addition this nutrient be precipitate with aluminum and iron. However, should study the possibility of its use in time or after liming, once application of this nutrient before liming can reduce the efficiency of phosphorus and increases mechanization cost. An alternative to the use rock phosphate after liming is used from acidification provided for nitrogen, as the nitrification naturally contributes to reduce soil pH. Thus, this study aimed to evaluate use of rock phosphate associated with nitrogen fertilizers in growth palisadegrass in Oxisol with low phosphorus. Were conducted three experiments, all in greenhouse at Universidade Federal do Mato Grosso, Campus Rondonópolis. Rock phosphate from Bayóvar have 29% of phosphorus in its composition, with 14% solubility in citric acid. Ammonium sulfate allows the use of phosphate rock in palisadegrass fertilization even after liming, while urea does not provide enough soil acidity to the use of this fertilizer. Therefore, for the use of rock phosphate associated with urea is necessary to apply 35% of this phosphate and 65% in the form of superphosphate. In order to reduce the cost of nitrogen fertilization and prevent a large drop in soil pH, was studied whether there is optimum ratio between urea and ammonium sulfate associated with rock phosphate. Maximum production palisadegrass fertilized with rock phosphate occurs when nitrogen is supplied 100% of ammonium sulfate, which is the lowest cost per kilogram of dry matter produced.